2021
DOI: 10.3390/su13116397
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Sustainability and Critical Thinking through Debate—A Case Study

Abstract: Transversal competences such as sustainability or critical thinking have become more important in the last decades in University teaching. The objective of this article is to assess the effectiveness of debate as a teaching method capable of fostering such competences in engineering students. To do this, a debate activity has been held facing two reasonable positions: Sustainable Development versus Degrowth. The research methodology consisted of performing this activity in the classroom (with 13 students in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Another session assigns each student a role within a structured debate of an example of sustainable design, which allows diverse and competing perspectives to be explored more fully than might be the case if we were discussing from our own positions. The effectiveness of debate as a teaching method capable of fostering competences of critical thinking and sustainability has been assessed positively in engineering students [4]. This accords with the positive experience of using debate as a formal mode of teaching in the MA Sustainable Design course; students declared themselves emboldened to explore the case study (Fairphone) from multiple dimensions, rather than just their own.…”
Section: How Students Learnmentioning
confidence: 87%
See 1 more Smart Citation
“…Another session assigns each student a role within a structured debate of an example of sustainable design, which allows diverse and competing perspectives to be explored more fully than might be the case if we were discussing from our own positions. The effectiveness of debate as a teaching method capable of fostering competences of critical thinking and sustainability has been assessed positively in engineering students [4]. This accords with the positive experience of using debate as a formal mode of teaching in the MA Sustainable Design course; students declared themselves emboldened to explore the case study (Fairphone) from multiple dimensions, rather than just their own.…”
Section: How Students Learnmentioning
confidence: 87%
“…The challenge is, then, how to ensure it is addressed in subject-based education. "How to develop these transversal competences and, at the same time, comply with the specific competences of each subject has been a recurrent objective in higher education" [4] (p. 1). This article examines the current state of pro-sustainability education in universities, specifically in the field of design.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the debate method promotes students' active engagement with materials as well as higher-order thinking. In fact, the debate method has been found to be among the best teaching methods to stimulate critical thinking and increases students' confidence in their public speaking skills (Combs and Bourne, 1989;Rodriguez-Dono and Hern andez-Fern andez, 2021). By having to assess and critique arguments of the opposing team, the method gives students the opportunity to practice professional disagreeing.…”
Section: The Debate Methodsmentioning
confidence: 99%
“…A study has also reported that with the debate class, students take a positive perception where it can improve verbal communication skills, reduce anxiety, actively prepare material so that the sentences delivered are organized, and hone self-confidence (Putri & Rodliyah, 2021). A case study in its findings agrees that the debate technique can improve students' critical thinking (Rodriguez-Dono & Hernández-Fernández, 2021).…”
Section: Steadiness/fear In Making and Delivering An Argumentmentioning
confidence: 96%